Eosinophilic esophagitis and somatic symptom disorder: A case report - Rodrigues, Márcia; Guerra Aguiar, Inês (BIRTH AND GROWTH MEDICAL JOURNAL, 2025)
This report describes the case of a 12-year-old male adolescent who presented with anxiety and somatic symptoms manifested as globus pharyngeus sensation and dysphagia following the diagnosis of eosinophilic esophagitis (EoE). Despite histologic and clinical improvement of EoE after treatment, the patient developed a persistent fear of swallowing solid food, accompanied by a sensation of a lump in the throat during meals. His psycho-affective immaturity was also noted. Due to the pervasiveness and functional impairment caused by anxiety and somatic symptoms, pharmacological treatment with oral sertraline solution was initiated. After four weeks of treatment, the patient showed significant improvement, regaining the ability to swallow solid food without the sensation of globus pharyngeus. In addition to pharmacologic therapy, cognitive-behavioral strategies were used to manage his symptoms. This case highlights the importance of considering the interplay between organic etiologies and psychological factors in the multidimensional management of anxiety and somatic symptom disorders.